Almost Fuzzy Compactness in L-Fuzzy Topological Spaces (Communications in Mathematical Research, 2021)
In this paper, the notion of almost fuzzy compactness is defined in $L$-fuzzy topological spaces by means of inequality, where $L$ is a completely distributiveDeMorgan algebra. Its properties are discussed and many characterizations of it arepresented.
Keywords: $L$-fuzzy topological space; $L$-fuzzy almost compactness; $L$-fuzzy compactness; almost fuzzy compactness.